Ratio Decadency Decision NO. 235/G/2019/PTUN.KT Against Notary Legal Remedies Affected with Notary Position Violations - ratna sari purba, Theresia; Rahayu, Mella Ismelina Farma (Kirana Publisher (KNPub), 2023)
Serious violations in the position of a notary are actions taken which are actions related to the obligations of a notary, the notary's code of ethics and the authority of a notary. The implication of committing a serious violation is dishonorably dismissed by those who have the authority, namely the Ministry of Law and Human Rights based on the recommendation of the MPWN. In the case with the PTUN Jakarta Decision in case No. 235/2019 , the notary holding the protocol in his case has signed a deed outside his area of office, the report of the incident issued the Indonesian Minister of Law and Human Rights regarding dishonorably dismissing someone in his position as a Notary, for having committed an act that violates ethics as a Notary . Type the research used in this research is normative by using secondary data as legal material. The ratio decidendi of the PTUN Jakarta decision in case No. 235/2019 did not consider the attribution authority given directly by law to the Ministry of Law and Human Rights in issuing KTUN which had implications for the dishonorable dismissal of a person in said KTUN from his Notary position , besides that the ratio decadence of the a quo case also did not take into account that there were no AAUP violations or ratio-Legis violations committed by the Tun Official in issuing a KTUN regarding the dishonorable discharge of a notary official in the a quo case